2022
DOI: 10.3390/gels8010034
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Sol-Gel Coatings Doped with Non-Toxic Corrosion Inhibitors for Corrosion Protection on AZ61 Magnesium Alloy

Abstract: Physiological human fluid is a natural corrosive environment and can lead to serious corrosion and mechanical damages to light Mg–Al alloys used in prosthetics for biomedical applications. In this work, organic–inorganic hybrid coatings doped with various environmentally friendly and non-toxic corrosion inhibitors have been prepared by the sol-gel process for the corrosion protection of AZ61 magnesium alloys. Effectiveness has been evaluated by pH measurements, optical microscopy, and SEM during a standard cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The corrosion inhibitor-loaded sol-gel coating is mainly achieved by incorporating appropriate inhibitors in the sol preparation process [ 59 , 60 ]. These corrosion inhibitors are stored in the prepared sol-gel coating.…”
Section: Bare Sol-gel Coatingsmentioning
confidence: 99%
“…The corrosion inhibitor-loaded sol-gel coating is mainly achieved by incorporating appropriate inhibitors in the sol preparation process [ 59 , 60 ]. These corrosion inhibitors are stored in the prepared sol-gel coating.…”
Section: Bare Sol-gel Coatingsmentioning
confidence: 99%
“…The natural corrosive environment of physiological human fluid can cause substantial corrosion and mechanical damage to light MgeAl alloys used in biomedical prosthesis. Rodrguez-Alonso et al [2] investigated the effectiveness of hybrid sol-gel coatings with and without corrosion inhibitors, such as L-cysteine, TiO 2 nanoparticles, 2aminopyridine, quinine, dimetyl glyoxime, and graphene oxide sheet, for the protection of AZ61 Mg alloy in Hanks' Balance Salt solution for 14 days immersion. The results demonstrated that adding an inhibitor to the sol-gel coating can increase corrosion performance greatly, and that it is an effective barrier for L-cysteine-doped hybrid sol-gel films.…”
Section: Summarizes the Anti-corrosion Properties Of Mgal-ldhs Coatin...mentioning
confidence: 99%
“…The recent transition to organic inhibitors is motivated by their enhanced inhibitory capacity, attributed to the presence of multiple heteroatoms and double bonds. This shift reflects a commitment to advancing corrosion protection methods in a more sustainable and environmentally conscious direction [ 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%